Russell and Cassirer as Leibniz’s Interpreters: On the Analytic and Synthetic Nature of Mathematical and Physical Knowledge - Laino, Luigi (Studia Kantiana, 2023)
In this paper, I aim to reconstruct the debate on Leibniz to which Russell’s and Cassirer’s monographs contributed eminently. This task is important both historically and epistemologically. In fact, their interpretations represented the apexes, at least at that time, of the logicist and the neo-Kantian philosophies of mathematics; on the other hand, they also paved the way for later developments of the discussion on the foundations of mathematics. The paper is divided into five sections. The first contained a brief introduction. In the second and third parts, I present Russell’s and Cassirer’s works to explain why they maintained that mathematics is synthetic. In the fourth section, I compare and contrast the reviews that they wrote about their books. Finally, in the fifth section, I propose a perspectivist interpretation of the dispute.